The Description of Knowledge and Attitudes of Parents in Performing First Aid for Hyperthermia in Preschool-Age Children - Moch. Azzam Miftahurroziqin; Peni Perdani Juliningrum; Iis Rahmawati (KHD-Production, 2023)
Hyperthermia is a health problem characterized by increased body temperature above normal due to thermoregulation failure. Improper hyperthermia treatment of children under five can result in complications such as dehydration and seizures. According to the concept of family-centered care, the family is one of the sources for the treatment of childcare. Involving the family can contribute to success in caring for sick children, not apart from knowledge and attitude in good health based on informed sources and a good environment. The study was intended to get a picture of the parent's knowledge and attitude in conducting hyperthermia first aid on preschool-age children on the coastal shore of the Situbondo county anchor. Research design uses observational/non-experimental study design with a descriptive study, and sample identification using a non-established method with an established sampling technique. The sample needed as many as 80 respondents with the inclusion and exclusion criteria. Data collection uses knowledge questionnaires and attitudes transmitted directly through posyandu; midwives and cadres of posyandu. Studies have found that of 80 respondents, most respondents were in the early adult age category (26-35), and some of those had 2 children. Most parents have a final elementary and high school education level with most of the employment status as housewives. Most of the respondents received information regarding the first treatment of hyperthermia from health officials. The level of parental knowledge is at a missing level and the parents' attitude is at a sufficient level. As a nurse, it is necessary to provide innovation in educating parents about first aid for hyperthermia in children with various health promotion media to change knowledge and attitudes, so that they can undergo better first aid behavior.